2009
DOI: 10.3791/1543
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Hippocampal Dentate Gyrus from Adult Mouse

Abstract: The hippocampus is one of the most widely studied areas in the brain because of its important functional role in memory processing and learning, its remarkable neuronal cell plasticity, and its involvement in epilepsy, neurodegenerative diseases, and psychiatric disorders. The hippocampus is composed of distinct regions; the dentate gyrus, which comprises mainly granule neurons, and Ammon's horn, which comprises mainly pyramidal neurons, and the two regions are connected by both anatomic and functional circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 5 publications
0
153
0
1
Order By: Relevance
“…For qRT-PCR, Western blot and BSP assay, mice were anesthetized and the bilateral DG was rapidly microdissected under a stereomicroscope, strictly according to procedures as described by Hagihara et al (2009). The mouse was deeply anesthetized, the brain was carefully dissected out from the skull and placed into ice-cold phosphate-buffered saline (PBS).…”
Section: Dissection Of Hippocampal Dg From Micementioning
confidence: 99%
“…For qRT-PCR, Western blot and BSP assay, mice were anesthetized and the bilateral DG was rapidly microdissected under a stereomicroscope, strictly according to procedures as described by Hagihara et al (2009). The mouse was deeply anesthetized, the brain was carefully dissected out from the skull and placed into ice-cold phosphate-buffered saline (PBS).…”
Section: Dissection Of Hippocampal Dg From Micementioning
confidence: 99%
“…To this aim, we dissected the DG from the remaining part of the hippocampus (collectively indicated as CA). The accuracy of our dissection was evaluated by measuring the mRNA levels of tryptophan 2,3-dioxygenase (TDO2) and TYRO3 protein tyrosine kinase 3 (Tyro3), two markers specifically expressed in the DG and in the CA regions, respectively (Hagihara et al, 2009), which revealed a clear separation of the two areas (Supplementary Figure S2). First, we assessed the total BDNF mRNA levels, finding that BDNF mRNA expression was higher in the DG compared with the remaining CA regions and that BDNF expression was modulated by exercise only in the DG area (area: F (1,44) = 106.8; Po0.0001; groups: F (3,44) = 14.38; Po0.0001; interaction: F (1,44) = 5.119; P = 0.004).…”
Section: Physical Exercise-induced Reduction Of Body Weight Gainmentioning
confidence: 99%
“…Furthermore, the thalamus/hypothalamus was removed using a Wecker Micro Dissecting Spatula (Roboz Surgical Instruments Inc.). The hippocampus was removed as described elsewhere (53). Finally, part of the cortex was removed with a fresh razor blade.…”
Section: Isolation Of Brain Regions and Dna And Rna Extractionmentioning
confidence: 99%